Cholinergic Stimulation of the Adult Zebrafish Brain Induces Phosphorylation of Glycogen Synthase Kinase-3 β and Extracellular Signal-Regulated Kinase in the Telencephalon - Mans, Robert A.; Hinton, Kyle D.; Payne, Cicely H.; Powers, Grace E.; Scheuermann, Nicole L.; Saint-Jean, Michael (Frontiers in Molecular Neuroscience, 2019)
The sequencing of the zebrafish genome, emergence of powerful gene-editing tools, and the development of in vivo imaging techniques have propelled the economical zebrafish into prominence as a biomedical research model. Neurodegenerative disorders with a cholinergic component, such as Alzheimer's and Parkinson's diseases, are currently modeled using zebrafish. Still, the utility of zebrafish as a research model will not be fully realized until their neurophysiological properties are thoroughly characterized. In mammals, the coupling of cholinergic receptors to the phosphorylation of glycogen synthase kinase-3 beta (GSK3beta) and extracellular signal-regulated kinase 1/2 (ERK1/2) is of critical importance to cognitive processes and imparts protection against neuropathogenic events. Similarly, it is known that cholinergic receptors are required for learning and memory in zebrafish, and that in vivo activation of cholinergic receptors induces transient changes in evoked synaptic transmission in the telencephalon. However, the intracellular events mediating cholinergic processes in zebrafish have yet to be elucidated. In the current study, an ex vivo drug treatment assay was used to demonstrate that carbachol-mediated cholinergic stimulation of the intact adult zebrafish brain induces phosphorylation of GSK3beta and ERK1/2 in the zebrafish telencephalon. These findings suggest GSK3beta and ERK1/2 may underly cognitive processes in zebrafish.